Pre-Prosthetic Management: Mandibular Alveoloplasty With Local Anesthesia - Indah Ayu Kusumawardhani; Nina Runting (CV. AFDIFAL MAJU BERKAH, 2026)
Pre-prosthetic surgery is essential to restore normal oral cavity function by reshaping and smoothing bone margins prior to denture fabrication. Alveoloplasty is a common surgical procedure performed to eliminate sharp bony projections and smooth the bone surface. This case report aims to present the management of mandibular alveoloplasty performed under local anesthesia prior to denture fabrication. A 52-year-old male patient presented to Soelastri Dental Hospital requesting denture fabrication. A prosthodontist referred the patient to an oral surgeon to address sharp bony projections in the left mandibular gingival region. Clinical intraoral examination revealed alveolar exostosis without signs of inflammation, though the area was tender upon palpation. Panoramic radiographic evaluation confirmed the presence of alveolar bone projections in the left mandibular region. The alveoloplasty procedure was performed using a mandibular inferior alveolar nerve block combined with local infiltration anesthesia. Bony projections and sharp alveolar ridges were smoothed and contoured to enhance denture retention and stability, as sharp ridges can cause irritation during denture wear. The incision on the alveolar ridge and the elevation of the mucoperiosteum were kept minimal to preserve vestibular depth. Irregular and sharp bone edges were trimmed and smoothed (reducing the height by 1–2 mm) using rongeurs, bone files, or bone burs, and the wound was closed with silk sutures. Alveoloplasty is a crucial oral surgery procedure for reshaping jawbone contours to ensure functional, aesthetic, and comfortable outcomes prior to denture fabrication.